2022
DOI: 10.1016/j.jsxm.2022.01.515
|View full text |Cite
|
Sign up to set email alerts
|

Are Endogenous Androgens Linked to Female Sexual Function? A Systemic Review and Meta-Analysis

Abstract: Background The benefits of treatment with testosterone (T) in women with loss of desire suggest that low androgens may distinguish women with sexual dysfunction (SD) from others; however, evidence on this point is lacking. Aim To answer the question: is there an association between endogenous levels of androgens and sexual function in women? Methods An extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 79 publications
0
15
0
Order By: Relevance
“…However, among postmenopausal females, adrenal DHEA becomes one of the major precursors of estrogens and androgens. A decrease in DHEA among postmenopausal woman can induce sexual dysfunction [24], diminished skin tone [25], and vaginal dryness [26]. Although DHEA values decreased in the present study, they were still within the normal range for both premenopausal females (1.12–7.43 ng/mL) and postmenopausal females (0.6–5.7 ng/mL) [27].…”
Section: Discussionmentioning
confidence: 55%
“…However, among postmenopausal females, adrenal DHEA becomes one of the major precursors of estrogens and androgens. A decrease in DHEA among postmenopausal woman can induce sexual dysfunction [24], diminished skin tone [25], and vaginal dryness [26]. Although DHEA values decreased in the present study, they were still within the normal range for both premenopausal females (1.12–7.43 ng/mL) and postmenopausal females (0.6–5.7 ng/mL) [27].…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, another important issue is related to the lack of blood androgens assessment in this study. Indeed previous study clearly showed that and serum levels of testosterone was significantly lower in SLE patients than control [ 30 ], and low androgen was associated with fatigue [ 31 , 32 ] and female sexual dysfunction in previous study [ 33 ]. A global consensus statement has recommended the treatment with testosterone in this kind of patients with sexual concerns [ 34 ].…”
Section: Discussionmentioning
confidence: 96%
“…8.2.5). Although there is no threshold for any androgen that can be used to diagnose women with FSD, a recent meta-analysis concluded that there appears to be a moderate association between endogenous total testosterone levels and sexual desire [14]. Studies on female rats treated with estradiol, testosterone, and aromatase inhibitors first suggested that aromatization may not be necessary for testosterone to increase the sensitivity of the response to male-related cues [15].…”
Section: Pathophysiology Of Low Desirementioning
confidence: 99%
“…All pathological and physiological conditions that determine lower androgen and free androgen levels, besides iatrogenic menopause, may result in diminished desire [14]. Among these, pregnancy, puerperium, lactation, pathological hyperprolactinemia, hypopituitarism, hypothalamic amenorrhea, adrenal insufficiency, primary ovarian insufficiency, and increased sex hormonebinding globulin (SHBG), which is common in women using hormonal contraception, are particularly important [30].…”
Section: Prevalence and Leading Etiologies Of Hsddmentioning
confidence: 99%